An Error Analysis on Dialogue Script Written by Eighth Grade of SMPN 3 Kota Jambi - Silfia, Efa (Jurnal Ilmiah Dikdaya, 2022)
In learning English especially in writing, the students made errors to write dialogue. They have lack of vocabulary and less idea in writing English sentence. They also need to consider about the grammatical components of English that differ from Indonesian language. The aim of this research was to describe errors made by the students in writing dialogue script. Thirty students from Eighth grade of SMPN 3 Kota Jambi were asked to write about free essay in dialogue script. All students writing are, then, analyzed in order to investigate students' errors. Based on findings of this research in linguistic category and surface strategy, it can be concluded that the students have difficulties in grammar (tenses, preposition, agreement, article), lexicon (vocabulary and spelling), punctuation for linguistic category and addition (double marking, regularization, simple addition), omission, misformation (regularization, archi- form, alternating form), misordering for surface strategy. Most students tend to have difficulties in spelling and omission.